PENGARUH STATUS EKONOMI ORANG TUA DAN MINAT BELAJAR TERHADAP HASIL BELAJAR KELAS X IPS DI SMAN 1 KOTA JAMBI - Apriliani, Wulandari; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2021)
Abstract This study aims to determine (1) the description of the economic status of parents, interest in learning, and learning outcomes of class X IPS in economic subjects at SMA Negeri 1 Jambi City. (2) The effect of the economic status of parents on the learning outcomes of class X IPS in economic subjects at SMA Negeri 1 Jambi City. (3) The effect of interest in learning on student learning outcomes of class X IPS at SMA Negeri 1 Jambi City. (4) The effect of the economic status of parents and interest in learning on the learning outcomes of class X IPS at SMA Negeri 1 Jambi City. This research design uses quantitative research methods, with data collection techniques through observation and questionnaires. Where the population in this study were 102 students with a sample of 83 students. The data processing techniques in this research are Validity Test, Reliability Test, Quantitative Descriptive Analysis, Homogeneity Test Normality Test, Simple Regression Test, Multiple Regression Test, and Hypothesis Test. The results of this study indicate that (1) the economic status of the parents obtained a TCR value of 80.65% with a good category, interest in learning to obtain a TCR value of 81.21% in a good category, and students who obtained a value above 7.6 %) students and students who score below the KKM are 35 (34%) students. (2) There is an effect of the economic status of parents on the learning outcomes of class X IPS in SMA Negeri 1 Jambi City of 2.410. (3) There is an effect of interest in learning on student learning outcomes of class X IPS in SMA Negeri 1 Jambi City of 2,394. (4) There is an effect of the economic status of parents and interest in learning on the learning outcomes of class X IPS in SMA Negeri 1 Kota with an Fcount of 3.840 with a significant value of 0.025. Thus, that parents and teachers play an important role in fostering student interest, because students' interest in learning is not only from the factors of parents and family but also from within the students themselves. In the learning process, every support has meaning, meaning and an important role in the growth and development of students' activities in carrying out learning interaction. Keywords: Parents' Economic Status, Learning Interest, Learning Outcomes.